3D acceptors with multiple A–D–A architectures for highly efficient organic solar cells. Issue 4 (20th March 2023) - Chen, Hongbin; Zhang, Zhe; Wang, Peiran; Zhang, Yunxin; Ma, Kangqiao; Lin, Yi; Duan, Tainan; He, Tengfei; Ma, Zaifei; Long, Guankui; Li, Chenxi; Kan, Bin; et al.
Abstract : Efficient 3D NFAs through central unit connection blaze a new trail in further molecular structural optimization of state-of-the-art NFAs. Abstract : Compared to the most-studied non-fullerene acceptors (NFAs) with linear skeletons, multi-dimensional NFAs with largely conjugated extensions in multiple directions may contribute to more efficient organic solar cells (OSCs) due to the potentially improved absorption, molecular packing and charge transport dynamics. Herein, a conjugated-skeleton connection mode assembled from central units of NFAs is developed, extending conventionally linear molecular skeletons towards three-dimensions (3D). The afforded 3D NFAs with specific A–D–A architectures in two directions demonstrate extremely low reorganization energy, fibrillar network film morphology, improved charge transport behavior and enhanced stability. After molecular geometry control by elaborate fluorine-induced noncovalently conformational locks, an exciting efficiency of 17.05% is achieved by CH8-1-based binary bulk-heterojunction OSCs, which is the highest value afforded by multi-dimensional acceptors thus far. Our success in constructing efficient 3D NFAs through easy central unit connection blazes a new trail in further molecular structural optimization of state-of-the-art NFAs.